MEMBACA, MENULIS KELAS AWAL (READING IN THE CLASSROOM) - Aulya Putri, Ramadhani; Dewi Yuli Trisnawati; Lasmi; Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Early-grade children' educational development greatly depends on their ability to read and write, two fundamental skills. These skills serve as the foundation for students' comprehension and mastery of other disciplines. Early learning is based on reading and writing abilities, which are essential for primary school pupils' social and academic growth. This article looks at the main obstacles to teaching reading in the early grades, efficient teaching strategies, and how technology might improve reading abilities. Students can acquire excellent reading skills and a lifelong love of reading through an all-encompassing and cooperative strategy that involves educators, families, and communities. The results suggest using a variety of instructional techniques and incorporating technology to produce reading experiences that are both interesting and long-lasting. By strengthening literacy, students are better prepared to meet the demands of future education and life.